DNA barcoding and molecular phylogeny of indigenous bacteria in fishes from a tropical tidal river in Malaysia - Rahman, Mohammad Mustafizur; Izuddin, Mohd Haikal; Khan, Najmus Sakib; John, Akbar; Naim, Mohd Azrul (Springer, 2018)
DNA barcoding along with molecular phylogeny can be used to taxonomic identification, characterization, and discovery of species and understand molecular relationships especially in term of species divergence. Thus, they facilitate biodiversity studies. Some studies have addressed DNA barcoding of bacterial samples from various sources. Unfortunately, the DNA barcoding of fish bacterial diversity has yet been studied especially in the tropical tidal river. Therefore, a study was conducted to (1) identify the observed bacterial isolates by comparing the partial sequence from an unknown sample to a collection of sequences from known reference samples, (2) know the taxonomic and phylogenetic identity of identified bacteria in the fish, and (3) know the abundance of fish bacteria in the Kuantan River. For this study, three commercially important fish, namely, Pristipomoides filamentosus, Cyclocheilichthys apogon, and Labiobarbus festivus were captured with gill nets from Kuantan River, Malaysia. Bacteria from skin, gill, and gut in fish were cultured at 35 C for 24 h in both nutrient and marine agars. Bacterial DNA were extracted using Bacterial Genomic DNA Isolation Kit following manufacturer’s specifications. IsolatedDNAwere quantified in NanoDrop 2000v and gel eluded in 1.5% agarose gel and visualized under gel visualizer. PCR products were out source sequenced at First Base Sdn.bhd using ABI sequencer under Sanger sequencing method. Sequences were trimmed using Sequence Scanner 2.0V. The aligned sequences were inspected by eye and edited to remove ambiguities based on PHRED scores and chromatogram. Fully aligned sequences were subjected to BLAST for nucleotide similarity search against 16S rRNA database. Best matched species was selected based on BLAST results and lowest genetic distance between known and unknown nucleotides. Genetic distance (sequence divergences) were calculated using the K2P (Kimura two parameter) distance model. Neighbor-joining (NJ) trees of K2P distances were created to provide a graphic representation of the patterning of divergence between species. This method identified a total of 11 fish bacteria, which taxonomically classified into Enterobacteriales, Pseudomonadales, Actinomycetales, and Bacillales. The range of pair-wise genetic distances between species of Enterobacteriales was lower than Bacillales. Similarly, within group mean genetic distance of Enterobacteriales (0.010) was lower than Bacillales (0.055). These results indicate that the identified bacteria species under Enterobacteriales are more closely related than bacteria species under Bacillales. The mean genetic distance between groups were genetically almost equally closed which was confirmed by overall mean diversity. Out of 11 species 7 were identified in Cyclocheilichthys apogon, 8 in Labiobarbus festivus, and 7 in Pristipomoides filamentosus. Overall mean bacterial abundance (CFU/g) were higher in C. apogon (6.68 103) compare to L. festivus (5.12*103) and P. filamentosus (5.20*103). Overall, highest bacterial abundances were observed in fish gut (6.62*103), followed by fish gill (5.78*103) and fish skin (4.60*103).